Fasting during Ramadan: efficacy, safety, and patient acceptability of vildagliptin in diabetic patients - Aziz KMA (Dove Medical Press, 2015)
Kamran MA Aziz Aseer Diabetes Center, Aseer Central Hospital, Ministry of Health, Abha, Saudi Arabia Abstract: Diabetes management during Ramadan fasting is challenging to the physician in terms of minimizing the risk of hypoglycemia. As compared to oral hypoglycemic agents (OHAs) and sulfonylureas (SUs), which carry a higher and significant risk of hypoglycemia, newer antidiabetic agents such as dipeptidyl peptidase-4 (DPP-4) inhibitors have demonstrated lower risk of hypoglycemia during Ramadan fasting, with better patient compliance. In addition to diabetes education and pre-Ramadan assessments, the physician should also consider use of DPP-4 inhibitors (such as vildagliptin) during Ramadan fasting to minimize the risk of hypoglycemia in type 2 diabetic subjects. Severe episodes of hypoglycemia have been demonstrated in recent research and clinical trials with OHAs/SUs. Conversely, these research observations have also demonstrated comparative safety and efficacy with lower risk of hypoglycemia associated with vildagliptin. Current research review has collected evidence-based clinical trials and observations for the drug vildagliptin to minimize the risk of hypoglycemia during Ramadan fasting, while at the same time focusing the role of diabetes self-management education (DSME), pre-Ramadan assessments, and patient care. Keywords: hypoglycemia, DPP4-inhibitors, oral hypoglycemic agents, Ramadan fasting, type 2 diabetes, vildagliptin